Varicose veins in the anterior accessory great saphenous vein system of the lower limb - V. I. Rusyn; F. M. Pavuk; M. I. Borsenko; N. M. Popovych; V. V. Rusyn (Сучасні медичні технології, 2025)
Aim. In order to improve the results of the treatment of patients with varicose veins and to prevent the recurrence of the disease, a quantitative analysis of the types of varicose veins in the anterior accessory great saphenous vein (GSV) system should be carried out according to the source of their reflux.